Sleep and awakening disorders in Parkinson’s disease: comprehensive approach to therapy - Marina Romanovna Nodel (Неврология, нейропсихиатрия, психосоматика, 2012)
The paper presents the specific features of the clinical presentation and pathophysiology of sleep and awakening disorders in patients with Parkinson’s disease (PD). It covers the current views of the role of chronobiological mechanisms in the regulation of sleep and awakening in PD. Major approaches to therapy for insomnia, para-, and hypersomnia in these patients are discussed. Data on the efficacy of melatonin in sleep and awakening disorders are given.